Electrocatalytic Synthesis of 1,2-Dioxolanes from Tetrasubstituted Donor–Acceptor Cyclopropanes - Oliver, Gwyndaf A.; Kolb, Simon; Werz, Daniel B. (Synlett, 2023)
An electrochemical method for the synthesis of 3,3,5,5-tetrasubstituted 1,2-dioxolanes from donor–acceptor cyclopropanes with quaternary donor positions is described. This catalyst-free strategy delivers radical cations after C(sp3)–C(sp3) cleavage by direct anodic oxidation of the strained carbocycle. A broad scope with regard to the cyclopropanes employed in the reaction is presented. Additionally, we propose a plausible mechanism for the reaction.
Keywords: donor–acceptor systems; cyclopropanes; dioxolanes; electrochemistry